Origin of the cosmos and self-organization in the work of charles sanders peirce - Da Silveira, Lauro Frederico Barbosa [UNESP] (Taylor & Francis, 2018)
The understanding of the cosmos on the basis of all available knowledge is a central theme in Peircean philosophy. Assuming the need for fallible metaphysical assumptions to be refuted or supported by scientific progress, Peirce deductively develops a teleological hypothesis about the evolution and Self-Organization of the universe. In discussing this topic, the chapter focuses on the following aspects of Peirce’s thought: the refusal to accept the unknowable; the evolutionary and self-organizing character of the universe; and the universal principle of habit acquisition and the law of mind, which treat the progressive harmony and perfection of the cosmos.